Doctoral Music Creativity: The Literary Repertoire of the Bangkok Metropolitan Low String Orchestra - Supattarachaiyawong, Watcharapong; Premananda, Weerachat (Parichart Journal, 2025)
“Doctoral Music Creativity: The Literary Repertoire of the Bangkok Metropolitan Low String Orchestra” is a creative composition for the Bangkok Metropolitan Orchestra. The compositional technique emphasizes the low-string instruments since there are limited repertoire that highlights low-string instruments’ identities. The research involved analyzing string techniques from orchestral excerpts used in the professional audition. The result of the research is a new composition for an orchestra started with 7 minutes of the Trio Overture for Cello, Double Bass, and Marimba followed by 40 minutes of full orchestral music which presents low-string identities.